2021
DOI: 10.1136/bmjopen-2020-038777
|View full text |Cite
|
Sign up to set email alerts
|

Organising Support for Carers of Stroke Survivors (OSCARSS): a cluster randomised controlled trial with economic evaluation

Abstract: ObjectiveInvestigated clinical effectiveness and cost-effectiveness of a person-centred intervention for informal carers/caregivers of stroke survivors.DesignPragmatic cluster randomised controlled trial (cRCT) with economic and process evaluation.SettingClusters were services, from a UK voluntary sector specialist provider, delivering support primarily in the homes of stroke survivors and informal carers.ParticipantsAdult carers in participating clusters were referred to the study by cluster staff following i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
51
0
16

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(67 citation statements)
references
References 27 publications
0
51
0
16
Order By: Relevance
“…One protocol for trial of a person-centered intervention for informal carers/caregivers of stroke survivors (Organising Support for Carers of Stroke Survivors [OSCARSS]) has been published since. 29 The steering group reviewed reports and helped assess inter-rater reliability. A data extraction table was created, but quality assessment using a risk of bias tool was not considered relevant or appropriate.…”
Section: Resultsmentioning
confidence: 99%
“…One protocol for trial of a person-centered intervention for informal carers/caregivers of stroke survivors (Organising Support for Carers of Stroke Survivors [OSCARSS]) has been published since. 29 The steering group reviewed reports and helped assess inter-rater reliability. A data extraction table was created, but quality assessment using a risk of bias tool was not considered relevant or appropriate.…”
Section: Resultsmentioning
confidence: 99%
“…A strength of this study is that the topics covered during all group sessions of the BISC intervention emerged from a review of the relevant literature, interviews with stroke carers and a nominal group consensus meeting with expert clinicians and researchers (Condon et al, 2019 ). Another key element of the intervention development process was patient and public involvement (PPI) and such a collaborative approach is recommended in intervention studies organising support for carers of stroke survivors (Patchwood et al, 2021 ). This allowed the tailoring of the intervention to the specific needs of the people providing care to stroke survivors as focused interventions have been found to be more effective and efficient (Panzeri et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, many interventions aimed at supporting carers of stroke survivors have been evaluated with some preliminary positive results (Araújo, Lage, Cabrita, & Teixeira, 2018 ; Day et al, 2021 ) and others reported more conclusive findings but with no evidence on clinical or cost-effectiveness (Patchwood et al, 2021 ). However, many of these interventions often neglect to address the physical and psychological well-being of carers and focus more on the provision of information and practical support for preparing to manage the complex needs of stroke survivors for the transition from hospital to home care.…”
Section: Introductionmentioning
confidence: 99%
“…24 Caregiver anxiety and depression were measured in 5 studies using the Hospital Anxiety and Depression Scale. [24][25][26]28,29 Other anxiety and depression measures included the Center for Epidemiological Studies Depression Scale, 19,21,30 Patient-Reported Outcomes Measurement Information System-Depression Short Form 8b, 35 Patient Health Questionnaire-9, 31 Beck Depression Scale, 27 Zung Self-rating Anxiety Scale, 28 and the Zung Self-Rating Depression Scale. 28 Several studies measured caregiver health-related quality of life using the same measures that were used for stroke survivors (ie, Older People's Quality of Life Questionnaire, 35 the Satisfaction with Life Scale, 32 and the EuroQol European Quality of Life EuroQol 24,25 ).…”
Section: Measurement Of Caregiver Outcomesmentioning
confidence: 99%
“…30 Positive aspects of caregiving were measured by the Chinese Version of the Perceived Benefits of Caregiving Scale, 20 Chinese Version of Positive Aspects of Caregiver Questionnaire, 32 and a Positive Appraisal of the Impact of Caring subscale from the Family Appraisal of Caring Questionnaire. 24 Caregiver anxiety and depression were measured in 5 studies using the Hospital Anxiety and Depression Scale. [24][25][26]28,29 Other anxiety and depression measures included the Center for Epidemiological Studies Depression Scale, 19,21,30 Patient-Reported Outcomes Measurement Information System-Depression Short Form 8b, 35 Patient Health Questionnaire-9, 31 Beck Depression Scale, 27 Zung Self-rating Anxiety Scale, 28 and the Zung Self-Rating Depression Scale.…”
Section: Measurement Of Caregiver Outcomesmentioning
confidence: 99%